LITERASI EKONOMI DALAM PANDANGAN FILSUF ADAM SMITH DAN KONTRIBUSINYA TERHADAP PENDIDIKAN - Selviani Selviani (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine economic literacy in the view of philosopher Adam Smith and its contribution to education. The research methodology used is a literature-based approach, which is based on books, notes, and summaries of previous research findings. The direct and indirect economic benefits of education, i.e. how it is viewed as an investment that yields long-term benefits. The notion of investing in education is developing rapidly, and it is increasingly widely accepted that the growth of the education sector is a necessary condition for the expansion of other development sectors in all countries.